(3MGTjI Ydi TQM SYO GdOjf aj GdUQas - (3GdMdHj, SQGL GdOjf, eMeO Hf YeQ, J (B850s ((3Wg Hf eMeOs)
(3ChdgG (B:s
(3fMeO Gddg Ydi Cf habfG UQa GdgeI fMh GdeYGdj hGdHjGf(B... (3hHYO ajbhd (B... (3eMeO Hf YeQ GdMdHj deG cGf eNJUQ(B... (3GdRfLGfj CLd bOQGs
(3BNQgG (B:s
(3hcdGgeG HGdZjf GdeYLeI fhY ef GdcdeGJ hGdQGHYI(B... (3bGd CHh SYjO(B: (3dG fXjQ dgPg GdBf(B. (3gPG BNQ eG CQOfG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B315s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B560s
(3cTa GdXfhf(B: (3L(B2(3, U(B1139s
(3GdCYdGe(B: (3L(B6(3, U(B315s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas